Differences in Serum Albumin and Globulin Levels on the Severity of Radiodermatitis in Breast Cancer Patients at a Tertiary Hospital in Yogyakarta - Novita Permatasari; Niken Indrastuti; Arief Budiyanto; Niken Trisnowati; Oktarina, Dyah Ayu Mira (Faculty of Medicine, Universitas Airlangga, 2026)
Background: Repeated and accumulated radiation exposure causes radiodermatitis in breast cancer patients. Lack of protein in the body can cause problems with wound healing induced by radiation exposure. Serum albumin and globulin levels are the most convenient protein components to assess. Purpose: To determine differences in serum albumin, serum globulin, and albumin/globulin (A/G) ratios for each grade of severity of radiodermatitis in breast cancer patients. Methods: This was an observational study with a cross-sectional design. Subjects were taken from the International Cancer Center at a tertiary hospital in Yogyakarta, who met the inclusion and exclusion criteria. A comparative analysis was performed to compare the means. Result: The number of radiodermatitis subjects were 32 patients, with 22 peoples in grade I, four peoples in grade II, and six peoples in grade III. The comparative test results showed differences in the average serum albumin levels for each severity grade: normal levels were obtained in radiodermatitis grades I and III, but low levels were obtained in grade II with a significant difference. There is a significant difference between serum albumin levels and each grade of severity of radiodermatitis. However, no significant results were obtained on serum globulin levels and A/G ratio. Conclusion: Serum albumin levels differ significantly according to the severity of radiodermatitis and may play a role in its progression, whereas serum globulin levels and A/G ratio are not associated. Albumin may be considered a potential clinical indicator in assessing radiodermatitis severity in breast cancer patients undergoing radiotherapy